Mapping of Soil Erosion Using Remote Sensing and GIS: Case of The Oued Bouhamdane Watershed (North-East of Algeria) - Khallef , Boubaker (Iraqi Journal of Science, 2023)
The northern region of Algeria is experiencing a real threat to the spatial extension of soil erosion. The Oued Bouhamdane watershed, part of this region, brings together all the natural and anthropogenic conditions that accelerate its degradation. This study is based on the use of remote sensing and GIS to map soil erosion in the Oued Bouhamdane watershed in north-eastern Algeria, using the Gavrilovic equation. The combination of data from different sources and field observation has made it possible to draw up a contextualized map of all the factors of soil erosion. Integrating the model into the GIS made it possible to give a first estimate of the annual volume of eroded soils, i.e., 14.57% of the total area of the Oued Bouhamdane watershed is affected, where soil losses are estimated on average at 941.13m3/Km2/year. This modest cartographic result is a perfect base for environmental monitoring and managing water resources in this watershed.